2003
DOI: 10.1177/136140960300800402
|View full text |Cite
|
Sign up to set email alerts
|

Workforce and workload: Are nursing resources used effectively?

Abstract: This paper describes key findings and implications from analyses of activity and workload of nurses of different grades and support workers based on data collected using Nursing Information Systems for Change Management (NISCM). 'Activity' refers to the amount of time on a shift spent on different tasks, and 'workload' refers to the number of patients in a variety of wards by demand/dependency group. The activity evidence is based on data from 5,208 staff recording their activity in 535 shift blocks in 19 hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…There is also evidence that practitioner roles are highly context specific [16]. Given the same title or grade, a nurse in one setting may carry out different roles and duties to those in a different setting [17].…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that practitioner roles are highly context specific [16]. Given the same title or grade, a nurse in one setting may carry out different roles and duties to those in a different setting [17].…”
Section: Introductionmentioning
confidence: 99%
“…Such changes are also occurring in healthcare systems throughout the world (Ross 1999, Chang & Wong 2001, Nkowane & Saxena 2004, Schober & Affara 2006. The global ageing population, worldwide shortages of staff, the increase in chronic disease, the growth of day surgery, the expansion of primary care and the continued reduction on the length of hospital stay all contribute to changing patterns of health care need and demand (Read et al 2001, Jenkins-Clarke & Carr-Hill 2003. In the UK, the development of these roles has been influenced by a number of other background factors.…”
Section: Introductionmentioning
confidence: 99%
“…Despite efforts to define nursing as a specific field, however, there is growing overlap in functions and activities of physicians, nurses and other NPCs [37]. Regardless of their level of education or experience, a study of nursing in the U.K. found that the different nursing groups regularly engage in the same range of direct and indirect nursing care [38]. In fact, the blurring borderlines between professional territories imply convergence of the "medical paradigm" and "nursing paradigm" and illustrate lack of agreement over the proper skill mix.…”
Section: Nursesmentioning
confidence: 99%